2014
DOI: 10.1016/j.dcn.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

White matter connectivity and aerobic fitness in male adolescents

Abstract: Highlights DTI was collected for 34 male adolescents, ages 15–17. Aerobic fitness related to white matter connectivity in frontal and motor tracts. HF had higher tractography streamline counts in CST and Fminor compared to LF. A negative relationship was seen between VO 2 peak and FA in the L CST. Exercise is an important environmental factor to consider during neurodevelopment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
58
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 56 publications
(84 reference statements)
12
58
3
Order By: Relevance
“…Finally, increasing FA in the CC suggests more efficient sensory, motor, and cognitive interaction taking place between the two hemispheres. [55][56][57] Positive effects on both CC and CST are in line with previously conducted studies that showed higher number of streamlines count in youths with higher self-reported fitness levels in CST and anterior CC 58 and the correlation between cardiorespiratory fitness parameters and FA suggested in healthy seniors, 59 females and multiple sclerosis patients, 60 but they have not been comprehensively demonstrated in a longitudinal setup. Thus, continuous practice of acquired physical skills improves fiber bundles in the brain implicated in primary and associative motor functioning.…”
Section: Discussionsupporting
confidence: 67%
“…Finally, increasing FA in the CC suggests more efficient sensory, motor, and cognitive interaction taking place between the two hemispheres. [55][56][57] Positive effects on both CC and CST are in line with previously conducted studies that showed higher number of streamlines count in youths with higher self-reported fitness levels in CST and anterior CC 58 and the correlation between cardiorespiratory fitness parameters and FA suggested in healthy seniors, 59 females and multiple sclerosis patients, 60 but they have not been comprehensively demonstrated in a longitudinal setup. Thus, continuous practice of acquired physical skills improves fiber bundles in the brain implicated in primary and associative motor functioning.…”
Section: Discussionsupporting
confidence: 67%
“…All linear mixed effect-modeling results (uncorrected p<0.05) were followed by permutations (n=1000) to obtain adjusted p-values, utilizing a threshold-free cluster enhancement algorithm [42]. Statistical trends were reported (corrected p<0.10).…”
Section: Methodsmentioning
confidence: 99%
“…The age and region of highest FA and lowest diffusivity vary substantially across reports and are likely attributable to many study differences, including scanner magnet field strength and manufacturer (Papinutto et al, 2013), acquisition protocol (Basser and Pierpaoli, 1996; Jones, 2004), quantification method, and participant factors such as age range (Yeatman et al, 2014), sex (Bava et al, 2011; Hasan et al, 2010; Herting et al, 2012; Wang et al, 2012), ethnicity, head motion (Kreilkamp et al, 2015; Yendiki et al, 2013), and even exercise (Herting et al, 2014). One way to confirm characterization of multifaceted dynamics of neurodevelopment is through longitudinal DTI study of adolescent white matter development.…”
Section: Introductionmentioning
confidence: 99%